2007
DOI: 10.1177/00343552070500020501
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Undergraduate Student Attitudes Toward Persons With Disabilities

Abstract: The Disability Social Relations Generalized Disability (DSRGD) Scale was used to explore the influence of the social context on attitudes toward persons with disabilities. The DSRGD Scale was based on the Disability Social Relationship (DSR) Scale (Grand, Bernier, & Strohmer, 1982; Strohmer, Grand, & Purcell, 1984). A sample of 1,013 undergraduate students completed the DSRGD. Principal axis factoring yielded three factors representing the three contextual subscales of Dating, Marriage, and Work. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 42 publications
2
72
2
9
Order By: Relevance
“…Despite other studies that support the independent effects of gender and experience (Hergenrather 2007), the findings of this research suggest that generalised educational interventions may be designed that do not need to be tailored to specific demographic groups. Further research may be warranted to replicate these findings, as well as to test for other potential demographic influences on attitude change such as ethnicity or stage of career-e.g.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Despite other studies that support the independent effects of gender and experience (Hergenrather 2007), the findings of this research suggest that generalised educational interventions may be designed that do not need to be tailored to specific demographic groups. Further research may be warranted to replicate these findings, as well as to test for other potential demographic influences on attitude change such as ethnicity or stage of career-e.g.…”
Section: Resultscontrasting
confidence: 71%
“…First, differences in attitude based on the gender of the research participant have been found (Findler et al 2007). For instance, Jaffe (1996) and Sandberg (1982) each found that female students were more accepting of cognitively impaired peers than males (Hergenrather 2007). Other research has found no difference between ratings of acceptance by males and females (Morgan and Wisely 1996;Peterson 1975;Tervo 2004) or found that males were more accepting of impaired peers than were females (Siperstein and Gottlieb 1977).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Öyle ki bayanlar, zaman geçirme, evlenme ve çalışma ile ilgili engellilere daha yüksek tutumlara sahiptir (Hergenrather ve Rhodes, 2007).…”
Section: Engellilere Karşı Olumsuz Tutumlarunclassified
“…Bu sonuç Hergenrather ve Rhodes (2007)'in kadınların engellilere yönelik daha olumlu tutumlara sahip olduğu iddiasını desteklemektedir.…”
Section: Sonuçunclassified
“…Numerous studies have looked at preservice teachers and their attitudes, sentiments and concerns about teaching children with disabilities [15][16][17]; but few have focused specifically on self-efficacy and its potential to direct preservice teacher beliefs in their own capabilities when working with these students [18,19]. There are also unique issues relating to the theory transfer into practice in teacher education with often limited detail regarding what goes on in a session in order to try and prepare students for conditions that will be found in the field [2,20,21].…”
Section: Introductionmentioning
confidence: 99%